2023
DOI: 10.3390/bioengineering10020145
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiafiltration: Technical and Medical Insights

Abstract: Despite the significant medical and technical improvements in the field of dialytic renal replacement modalities, morbidity and mortality are excessively high among patients with end-stage kidney disease, and most interventional studies yielded disappointing results. Hemodiafiltration, a dialysis method that was implemented in clinics many years ago and that combines the two main principles of hemodialysis and hemofiltration—diffusion and convection—has had a positive impact on mortality rates, especially when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
11

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 133 publications
7
31
0
11
Order By: Relevance
“… 105 Despite these promising findings, concerns about participant attrition during follow-up in these trails may have hindered widespread HDF adoption outside of Europe and Japan. 106 This is despite an individual-participant meta-analysis of four randomised controlled trials showing a reduction in all-cause mortality and cardiovascular mortality with high-dose HDF compared to HD. 107 Recently, the landmark CONVINCE study, a randomised-controlled trial of 1360 patients randomised to high-dose HDF and HD, demonstrated an absolute risk reduction in mortality of 4.6% (HR 0.77, 95% CI: 0.65–0.93).…”
Section: Human-centred Care As a Model To Address Unmet Needs In Chro...mentioning
confidence: 99%
“… 105 Despite these promising findings, concerns about participant attrition during follow-up in these trails may have hindered widespread HDF adoption outside of Europe and Japan. 106 This is despite an individual-participant meta-analysis of four randomised controlled trials showing a reduction in all-cause mortality and cardiovascular mortality with high-dose HDF compared to HD. 107 Recently, the landmark CONVINCE study, a randomised-controlled trial of 1360 patients randomised to high-dose HDF and HD, demonstrated an absolute risk reduction in mortality of 4.6% (HR 0.77, 95% CI: 0.65–0.93).…”
Section: Human-centred Care As a Model To Address Unmet Needs In Chro...mentioning
confidence: 99%
“…This deposit layer, whose significance has been recognised long ago [ 13 , 17 ], is often referred to as “secondary membrane” or fouling/’gel’ layer [ 17 ]. As noted below, the physico-chemical protein/polymeric-material interactions, also significantly affect albumin leaking to dialysate, due to the reduced membrane porosity and permeability caused by the adsorbed/deposited proteins [ 3 , 15 , 18 ]. In addition, it should be stressed that protein adsorption and fouling-layer/gel formation, is related to other complicated phenomena, including albumin unfolding/denaturation and ‘competitive adsorption’ among the most abundant proteins (i.e.…”
Section: Albumin Losses During Haemocatharsismentioning
confidence: 99%
“…Many studies (e.g. [ 1 3 ]), show that, in particular OL-post-HDF (online, post-dilution haemodiafiltration), involving large transmembrane/ultrafiltration rate (and the concomitant large substitution volume), is quite beneficial leading to reduced mortality [ 1 , 3 ]. However, there is concern that, under such conditions (involving relatively high-permeability membranes), excessive albumin losses may occur, which are possibly associated with hypoalbuminemia, at least for some ESRD-patient categories [ 4 ].…”
Section: Introduction—scopementioning
confidence: 99%
“…To achieve the treatment targets that were shown during the CONVINCE trial to impact patient outcomes, the dialysis session must be performed with a dialyzer that enables high ultrafiltration volumes and high middle molecule removal [11]. Dialyzer performance is mainly determined by the dialyzer membrane, which may differ in material composition, geometry, or structure, including the pore size and properties of the blood-facing surface [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The novel FX CorAL dialyzer contains such a hydrophilic membrane with increased PVP content on the blood-side surface and was shown in clinical and experimental studies to induce lower protein adsorption than other commonly used dialyzers in clinical practice [12,[36][37][38]. Moreover, the FX CorAL dialyzer was previously compared to other polysulfone-, polyethersulfone-, and cellulose-based dialyzers with regard to performance and hemocompatibility [11,12,19,[36][37][38][39][40][41]. Experimental studies showed a strong correlation between the low protein adsorption by the FX CorAL and the good hemocompatibility profile as well as low sieving coefficient changes over time [19,38].…”
Section: Introductionmentioning
confidence: 99%